Effect of Hydrolysis Time and Acid Concentration on Yield and Quality of Glucose Syrup from Kepok Banana Starch (Musa paradisiaca L.) - Tri Suci Mayasari (Central Research Institute For Agriculture, 2022)
This reseach was done to know the effect of different hydrolyzing time and acid concentrate to the rendemen and quality of glucose syrup from kepok banana starch. This reseach used complete randomized design model (CRD) 4 x 4 consisted of 2 factors, factor number 1: hydrolyzing time consisted of 4 levels i.l; T1 = 2 hours, T2 = 2,5 hours, T3 = 3 hours and T4 = 3,5 hours., factor 2: acid concentration consisted of 4 levels i.l; K1 = 0,04 N, K2 = 0,06 N, K3 = 0,08 N and K4 = 0,10 N. Statistical analysis was done on rendemen, water content, glucose content, viscosity, TSS, sweetness and organoleptic values of taste and colour. The results showed that hydrolizing time gave highly significant difference effect on rendemen, water content, glucose content, viscosity, TSS, sweetness and organoleptic value of taste and colour. The acid concentration gave highly significant difference effect on rendemen, water content, glucose content, viscosity, TSS, sweetness and organoleptic value of taste and colour. The combination of hydrolyzing time and acid concentration gave highly sicnificant difference effect on rendemen and sweetnes but no difference on water content, glucose content, viscosity, TSS and organoleptic value of taste and colour. The best result from this reseach used hidrolizing time 3,5 hours and acid concentration 0,1 N.